Probiotic Prophylaxis of Neonatal Jaundice - Tatyana Itova; Victoria Georgieva (Journal of Biomedical & Clinical Research, 2022)
We investigated the effect of the administration of probiotics (PB) for the prevention of neonatal jaundice (NJ) in 315 full-term newborns (NBs). We grouped them according to the type and duration of PB intake: A – 5 days L. rhamnosus; B – 5 days L. reteri; C – 5 days B. animalis; D – 30 days L. rhamnosus; E – 30 days L. reuteri, F – 30 days B. animalis; G – without PB. Bilirubin (BR) was measured from 1st to 5th, on 14th, and on 28th day. The incidence of pathologic NJ in groups A&D, B&E, C&F, and G was 37, 36, 29, and 44%, respectively. During first five days, the lowest BR levels were found in Group C, the highest in Group G. BR levels on 14th and 28th days were not significantly different between groups A and D, B and E, C and F. The lowest levels of BR on the same days were found in group F and the highest in group E. The prophylactic use of L. rhamnosus, L. reuteri and B. animalis in full-term NBs significantly reduced the incidence and continuance of NJ. Duration of taking PB significantly affects the development of NJ. The most pronounced effect was when B. animalis was added.